Value-Based Leadership of Islamic Education Teachers and Its Role in Disciplinary Religious Practice Formation: A Qualitative Case Study in an Indonesian Public School - Muaddyl Akhyar; Zukdi, Ilpi; Nurfarida Deliani (Jurnal Pendidikan Islam, 2024)
Purpose – This study aims to explore the contribution of Islamic Religious Education (IRE) teachers' leadership competencies in shaping students’ discipline in religious observance at SMPN 2 Sintoga. The research addresses an empirical gap in the literature, which seldom links the leadership of IRE teachers to students’ worship practices within formal educational settings. Design/methods/approach – A qualitative approach was employed using an intrinsic case study method. Data were collected through participatory observation, semi-structured interviews, and document analysis involving IRE teachers, the school principal, and students. Thematic analysis was conducted with methodological triangulation and validated through member checking. Findings – The leadership of IRE teachers plays a strategic role in fostering students’ religious discipline through the habituation of congregational prayer, Qur’anic recitation, and motivational approaches. Among the 24 eighth-grade students interviewed, more than two-thirds reported a shift from reluctance to regular engagement in religious practices. Leadership strategies included cross-functional coordination, reward-and-sanction systems, and consistent spiritual guidance. Research implications – The results offer practical implications for educators and policymakers in designing character education programs rooted in daily worship practices, positioning religious teachers as moral and spiritual change agents.